Effect of oligonucleotide MT01 delivered by N-isopropylacrylamide modified polyethyleneimine for bone regeneration - Zhang, Qian; Qu, Xingyuan; Liang, Chen; Li, Hongyan; Du, Siyu; Wang, Chang; Xie, Yuandong; Zheng, Yi; Wang, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: This study aimed to investigate the regulatory effect of N-isopropylacrylamide-modified polyethyleneimine (PEN)-delivered oligodeoxynucleotide (ODN) MT01 on bone regeneration in vitro and in vivo. Methods: A polyethylenimine (PEI) derivative, PEN, was constructed through Michael addition and employed as a carrier for ODN MT01 transfection. PEN/MT01 nanocomposites were characterized using agarose gel retardation assay, size distribution, zeta potential and transmission electron microscopy. The Cell Counting Kit-8 (CCK-8) assay was used to detect the effect of PEN on cell viability. Alkaline phosphatase (ALP) staining was used to detect the osteogenic differentiation ability of PEN/MT01 nanocomposite. Real-time quantitative PCR (q RT-PCR) and enzyme-linked immunosorbent assay (ELISA) were used to detect the regulatory effects of PEN/MT01 nanocomposite on osteogenic differentiation gene expression. Rat model was observed using the skull defect method and verified using micro-computed tomography (CT), serum biochemical indices, hematoxylin and eosin (H&E) staining and Immunohistochemistry (IHC). Results: PEN had good biological properties and could deliver MT01 well to achieve efficient transmission of MT01. PEN/MT01 nanocomposites were effectively transfected into MC3T3-E1 cells at a ratio of 6.0. CCK-8 assay displayed that PEN had no cytotoxicity to MC3T3-E1 cells. Additionally, PEN/MT01 nanocomposites could promote the expression of osteogenic genes. In vivo results revealed that PEN/MT01 nanocomposites could promote bone regeneration more effectively than the other groups. Conclusion: PEN has good biocompatibility and low toxicity, which is a good carrier for ODN MT01. PEN-delivered MT01 can be potentially employed as a useful approach to achieving bone regeneration.